Effect of pretreatment with alkali on the anaerobic digestion characteristics of kitchen waste and analysis of microbial diversity - Zhen, Xiaofei; Li, Shange; Jiao, Ruonan; Wu, Wenbing; Dong, Ti; Liu, Jia (Green processing and synthesis, 2023)
Kitchen waste contains high contents of organic matter and moisture, and it is prone to biodegrade and decompose to give odors. If not collected and transported promptly or treated improperly, it is highly likely to pollute the environment and spread diseases. Because the lipid content in kitchen waste is high and a portion of organic matter is not subject to hydrolysis, the development of anaerobic digestion technology has been greatly limited. Kitchen waste was pretreated with NaOH, KOH, and Ca(OH) with different concentrations, and 50 days sequencing batch mesophilic anaerobic digestion experiments were conducted. This study sheds light on the pollution reduction and energy generation of kitchen waste. The results are as follows: (1) The lipid content of kitchen waste could be reduced, and the concentration of dissolved organic matter could be increased by pretreating with alkali. The degradation rate of kitchen waste lipid reached a maximum of 50.51%, if 3% NaOH was added, and the soluble chemical oxygen demand concentration was increased by 235.3%. (2) The cumulative methane (CH ) output and biogas production efficiency were improved in the anaerobic digestion process with kitchen waste pretreated with alkali. The maximum daily gas output of kitchen waste pretreated with NaOH and KOH took place on the 11th to 12th day, with the biogas production efficiency of 40.4 and 45.2 mL·g·VS . The cumulative CH output was increased from 370.2 mL·g·VS (untreated) to 393.1 and 434.1 mL·g·VS , respectively. In addition, the concentration of CH in biogas was increased from 54.8% (untreated) to 59.1% and 61.7%, respectively. (3) The Chao1 and Ace values of bacteria were increased first and then decreased. On the 10th day, the diversity of bacteria reached the highest value, and on the 20th day, the diversity of archaea reached its maximum. Therefore, it was verified that the improvement in the hydrolysis acidification efficiency and degree was crucial for the rapid and complete anaerobic digestion reactions.